Exophony as Practice of De- and Reterritorialization: Spatial and Linguistic Displacement in Early War Diaries from Ukraine - Seidel, Anna (Porównania, 2025)
This article explores the spatial and linguistic crises faced by Ukrainian writers in the aftermath of the Russian invasion of 2022. Through the analysis of three diaries—Andrey Kurkov’s Diary of an Invasion, Yevgenia Belorusets’ Anfang des Krieges, and Jelena Jeremejewa’s Seit September will ich nach Kiew—it examines the phenomenon of exophony, or writing in a foreign language, as a response to war and forced migration. The study shows how these writers, navigating both physical and linguistic dislocation, shift from Ukrainian or Russian to German or English. This linguistic shift symbolizes a productive break with national and cultural contexts and can be understood as a practice of de- and reterritorialization. The article offers new insights into the properties of exophonic writing in political conflicts, where language becomes a tool of resistance and identity transformation.